STRATEGI GURU DALAM MEMBANGUN KEPERCAYAAN DIRI SISWA MELALUI DISKUSI KELOMPOK PADA MATA PELAJARAN SENI BUDAYA DI SEKOLAH UPT SMP NEGERI 35 MEDAN - Sani Susanti, Azzuhratul Khalisa Hrp, Veronika Br Sinuhaji, Seviyana Chaira Br Tarigan, Yesi Okta Hu (CV. ADIBA AISHA AMIRA, 2024)
This study explores the role of group discussions in enhancing students' self-confidence. Based on theories of developmental psychology and education, a qualitative approach was used with observation and semi-structured interviews. The results indicate that group discussions enable students to interact, speak, and listen more confidently. By providing a supportive environment and appropriate strategies, group discussions can boost students' self-confidence. The implication is that teachers need to utilize various group discussion techniques to create supportive learning experiences and foster students' self-confidence.